Molecular Docking Of Quercetin As An Anti-Breast Cancer Agent - Purnaningtyas, Sri Rahayu Dwi; Andaririt, Devita Riafinola (Griya Eka Sejahtera, 2025)
Background: Breast cancer is a major global health problem and a leading cause of death in women. Flavonoid compounds, particularly quercetin, have been extensively studied for their diverse pharmacological activities, including antioxidant, anti-inflammatory, and anticancer properties. Advances in computational technology in pharmaceutical and medicinal chemistry, particularly molecular docking, offer opportunities to predict interactions between ligands and target receptors quickly, efficiently, and at low cost. This study aimed to identify Molecular Docking Of Quercetin As An Anti-Breast Cancer Agent.Methods: The ligand compounds were obtained from PubChem and the receptor clusters were obtained from the Protein Data Bank. Instrumens used VivoBook_AsusLaptop X409JB Intel ® Core ™ i3-1005G1 CPU @1.20GHz 12 RAM. The independent variables of this study were Quercetin and Doxorubicin to Cyclin-Dependent Kinase 6 (CDK6).Results: Molecular docking results show that quercetin has an average binding affinity value of –6.19 kcal/mol, while the positive control doxorubicin has an average value of –7.3 kcal/mol against the Cyclin-dependent kinase 6 (CDK6) receptor. Amino acid similarities were found in the receptors for quercetin and doxorubicin. The same bound amino acids were found on the 3NUP, 3NUX, and 4EZ5 receptors with Van Der Walls Bond. Amino acid similarities were found in the receptors for quercetin and doxorubicin. The 4NUP receptor contains the same amino acids: Phenylalanine (A:164) and Histidine (A:143), while the 3NUX receptor contains Lysine (A:26), Valine (A:45), Valine (A:27), and Phenylalanine (A:164). Meanwhile, the 4EZ5 receptor has the same amino acids, namely Glycine (A:22), Glycine (A:20), and Asparagine (A:104). This indicates a similarity in the mechanisms of action between quercetin and doxorubicin.Conclusion: Quercetin has great potential as a candidate for breast cancer treatment